2012
DOI: 10.1163/18759866-08103001
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic position and taxonomy of Cycloseris explanulata and C. wellsi (Scleractinia: Fungiidae): lost mushroom corals find their way home

Abstract: The scleractinian species Psammocora explanulata and Coscinaraea wellsi were originally classified in the family Siderastreidae, but in a recent morpho-molecular study it appeared that they are more closely related to each other and to the Fungiidae than to any siderastreid taxon. A subsequent morpho-molecular study of the Fungiidae provided new insights regarding the phylogenetic relationships within that family. In the present study existing molecular data sets of both families were analyzed jointly with tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 62 publications
2
77
0
Order By: Relevance
“…Scleractinian taxa and other Anthozoa with skeletons commonly preserved as fossils including the octocorals Isis, Heliopora, and Tubipora were included in the analysis (see Supplementary Data Table 3). New identifications were based on generic-level synonyms in Wells (1956), updated with more recent revisions (Wijsman-Best 1974, 1976, 1980Veron et al 1977;Veron and Pichon 1980;Cairns 1989Cairns , 1997Cairns , 1998Cairns , 2001Hoeksema 1989;Hoeksema and Borel-Best 1991;Cairns and Zibrowius 1997;Veron 2000;Kitahara and Cairns 2009;Benzoni et al 2010Benzoni et al , 2012aBenzoni et al , 2012bBudd et al 2012). In some cases, only genus-level determinations were attempted resulting in undivided genera including Ceratophyllia, Ctenella, Cyclolites, Dendracis, Isis, Lophelia, Physogyra, Stylocoenia, and Tropidocyathus.…”
Section: Taxonomymentioning
confidence: 99%
“…Scleractinian taxa and other Anthozoa with skeletons commonly preserved as fossils including the octocorals Isis, Heliopora, and Tubipora were included in the analysis (see Supplementary Data Table 3). New identifications were based on generic-level synonyms in Wells (1956), updated with more recent revisions (Wijsman-Best 1974, 1976, 1980Veron et al 1977;Veron and Pichon 1980;Cairns 1989Cairns , 1997Cairns , 1998Cairns , 2001Hoeksema 1989;Hoeksema and Borel-Best 1991;Cairns and Zibrowius 1997;Veron 2000;Kitahara and Cairns 2009;Benzoni et al 2010Benzoni et al , 2012aBenzoni et al , 2012bBudd et al 2012). In some cases, only genus-level determinations were attempted resulting in undivided genera including Ceratophyllia, Ctenella, Cyclolites, Dendracis, Isis, Lophelia, Physogyra, Stylocoenia, and Tropidocyathus.…”
Section: Taxonomymentioning
confidence: 99%
“…For example, the highly speciose genus Balanophyllia Wood, 1844, is exclusively composed of solitary species but a phylogenetic reconstruction of dendrophylliids demonstrated the extensive polyphyly of this genus (Arrigoni et al, 2014c). Also, the genus Cycloseris Milne Edwards & Haime, 1849, originally consisted of monostomatous and free-living species (Hoeksema, 1989) but new molecular and micromorphological data showed that the polystomatous and attached species C. explanulata (van der Horst, 1922), C. mokai (Hoeksema, 1989) and C. wellsi (Veron & Pichon, 1980) belong to this genus (Benzoni et al, 2012b;Gittenberger et al, 2011;Hoeksema, 2014). Again, the monostomatous Verrillofungia Wells, 1966, is now considered a junior synonym of the polystomatous genus Lithophyllon Rehberg, 1892, based on a combined morpho-molecular approach (Gittenberger et al, 2011).…”
Section: The Relevance Of Being Solitarymentioning
confidence: 99%
“…For the purposes of this study the following taxonomic classification schemes were used: Wallace et al (2012) for Acropora and Isopora; Gittenberger et al (2011) and Benzoni et al (2012a) for Fungiidae; Benzoni et al (2010) for Psammocora; Budd et al (2012) and Huang et al (2014) for Lobophylliidae, Merulinidae, Montastraeidae and Diploastraeidae; Razak and Hoeksema (2003) for Millepora; and Veron (2000) for all taxa that have not been revised recently. Historical data is summarized from the surveys conducted by James Maragos (Environmental Resources Section 1986; Donaldson et al 2007) and the synonomies have been updated as per the taxonomic schemes above.…”
Section: Taxonomy and Historical Datamentioning
confidence: 99%